Methyl Ferulic Acid Attenuates Human Cardiac Fibroblasts Differentiation and Myocardial Fibrosis by Suppressing pRB-E2F1/CCNE2 and RhoA/ROCK2 Pathway - Liao, Rongheng; Qi, Zhen; Tang, Ri; Wang, Renrong; Wang, Yongyi (Frontiers in Pharmacology, 2021)
Background Myocardial fibrosis is a key pathological process after myocardial infarction, which leads to poor outcomes in patients at the end stage. Effective treatments for improving prognosis of myocardial fibrosis are needed to be further developed. Methyl Ferulic Acid (MFA), a biologically active monomer extracted and purified from the Chinese herbal medicine, is reported as an attenuator in many diseases, in this study, we aim to reveal the role it plays in myocardial fibrosis after myocardial infarction and its possible mechanism. Results Firstly, in TGF-β1 induced human cardiac fibroblasts (HCFs) we found that MFA attenuated the expression of fibrosis related proteins and the ability of migration and proliferation. Then, myocardial fibrosis after myocardial infarction models on mouse were built to reveal the vivo affection of MFA, after 21 day of treatments, fibrosis areas, cardiac function and expression of fibrosis related proteins were all improved in MFA treated group than myocardial infarction group. Finally, to elucidate the mechanism of phenomenon we observed, we found that MFA attenuated HCF differentiation after myocardial infarction by suppressing the migration and proliferation in HCFs, which was by suppressing pRB-E2F1/CCNE2 and RhoA/ROCK2 pathway. Conclusion Our findings showed that MFA attenuated the expression of fibrosis related proteins and the ability of migration and proliferation in HCFs, improved the cardiac function of myocardial infarction mice at the same time, the mechanism of that is by suppressing pRB-E2F1/CCNE2 and RhoA/ROCK2 pathway.